Identifying and prioritising the key components of a Quality Improvement Network for allied health professionals and psychological therapists: a group concept mapping project. Issue 1 (30th January 2023) - Robinson, Lisa J; Butler, Hannah V; Hackett, Kate L
Abstract : Introduction: Despite growing enthusiasm for quality improvement (QI), the complexities of modern healthcare continue to create gaps in our ability to consistently deliver the most effective and efficient care for patients, and improvement activities often fail to achieve widespread uptake even when there is robust evidence of their benefits. Methods: We undertook a novel, mixed methods evaluation and planning project using group concept mapping (GCM) methodology to identify and prioritise the ways in which our recently established Quality Improvement Network (QIN) could support allied health professionals, psychological therapists and administrative staff in their daily work to improve patient outcomes and experience. Mid-level leaders across our therapy services department contributed towards a statement generation activity and individually sorted these statements into themes. Each statement was rated for perceived importance and current success. Multidimensional scaling and hierarchical cluster analysis were applied to the sorted data to produce themed clusters of ideas within concept maps. Priority values were applied to these maps to identify key areas for future QIN activity. Results: Overall, 34 participants took part in ideas generation, 20 in sorting and 30 in the rating activity. A five-item cluster map was agreed on, containing the following named clusters: data support; practical skills and training; time and resources; embedding a QI culture; and sharing ideas and working together. Statements contained within each of the five clusters highlight the importance of supporting a range of activities spanning the technical and human aspects of QI at an individual, group/team, organisation and wider systems level. Conclusion: GCM provided a structured and systematic approach for identifying the perceived support needs of allied health professionals, psychological therapists and administrative support staff in relation to QI. The findings from this project provide a useful benchmark from which to track targeted QI support in an applied healthcare setting.